Textbook of Speaking Learning Oriented on Reflective Approach and Integration of Local Wisdom - Susrawan, I Nyoman Adi; Erawan, Dewa Gede Bambang; Murtini, Ni Made Wersi; Sari, Rita Widiya; Raidah S, Huriah (Jurnal Pendidikan dan Pengajaran, 2025)
Students in Indonesian language education programs exhibit limited speaking skills, particularly in fluency, clarity, and depth of information. To bridge this gap, this study aims to create a speaking textbook incorporating Tri Hita Karana. This Research and Development (R&D) used the ADDIE approach. The study subjects included six specialist language education experts, a local cultural expert, and a speaking skills instructor, and it was tested on nine third-semester students. Data were collected through observation, semi-structured interviews, and pre-/post-tests. The research instruments used questionnaires and test items. Data analysis techniques used qualitative and quantitative descriptive approaches. The study results showed that the approved textbook received excellent ratings for reflective scaffolding (M = 4.7) and cultural relevance (M = 4.2). The pilot test showed substantial improvements in speaking performance; 80% of students said that reflective exercises improved self-assessment, and 75% effectively integrated Tri Hita Karana ideas into academic and social discussions. It was concluded that the textbook successfully fostered self-confidence, critical thinking, and culturally informed speaking skills. Furthermore, this study implies that reflective and contextually relevant materials can enhance the theory and practice of speaking education.